2021
DOI: 10.1002/ppul.25617
|View full text |Cite
|
Sign up to set email alerts
|

The association of lung function changes with outcomes in children with bronchiolitis obliterans syndrome after hematopoietic stem cell transplantation

Abstract: Background Bronchiolitis obliterans syndrome (BOS) is a life‐threatening respiratory complication of allogeneic hematopoietic stem cell transplantation (HSCT). Although pulmonary function testing is crucial for monitoring BOS, little information exists on the association of these test results with outcomes in children with BOS. Objectives The purpose of this study was to determine the correlation between changes in lung function after BOS diagnosis and long‐term outcomes. Methods A total of 428 children underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
9
0
2
Order By: Relevance
“…Declining lung function is a defining characteristic in bronchiolitis obliterans syndrome (BOS), however the clinical implications of lung function changes in BOS are unknown. Jung et al 50 | 2207 into this issue, Hardie et al 51 performed a retrospective review of testing (CPET). Although the majority (64%) of patients reported dyspnea on exertion, pulmonary limitation during exercise was present in only 3% of the study population, and there was no correlation between CPET results and symptoms of dyspnea or chest pain on exertion.…”
Section: Physiologic Assessments In Pediatric Respiratory Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Declining lung function is a defining characteristic in bronchiolitis obliterans syndrome (BOS), however the clinical implications of lung function changes in BOS are unknown. Jung et al 50 | 2207 into this issue, Hardie et al 51 performed a retrospective review of testing (CPET). Although the majority (64%) of patients reported dyspnea on exertion, pulmonary limitation during exercise was present in only 3% of the study population, and there was no correlation between CPET results and symptoms of dyspnea or chest pain on exertion.…”
Section: Physiologic Assessments In Pediatric Respiratory Diseasementioning
confidence: 99%
“…Declining lung function is a defining characteristic in bronchiolitis obliterans syndrome (BOS), however the clinical implications of lung function changes in BOS are unknown. Jung et al 50 examined the relationship between lung function decline and clinical outcomes in patients with BOS following allogenic hematopoetic stem cell transplantation. They found that a rapid decline in FEV 1 in the first 3 months after BOS diagnosis correlated with poor clinical outcomes, including death, need for lung transplantation, or oxygen therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Mean decline in forced expiratory volume in one second (FEV 1 ) (1.07% predicted and 0.075 in Z ‐score annually) was noted, with preservation of FVC, over an average follow‐up period of 8 years, suggesting ongoing lung growth despite persistent obstruction. Jung et al 48 reported on 21 patients with BO syndrome (patients with CT and PFT findings consistent with BO but lacking a biopsy) from a cohort of 428 who received HSCT from 2006 through 2017 at Asan Medical Center in Seoul. They also noted a high degree of morbidity and mortality with eight deaths (38%), and five (24%) progressing to lung transplantation.…”
Section: Children's Interstitial and Diffuse Lung Disease (Child)mentioning
confidence: 99%
“…(1)(2)(3)(4) Testes de função pulmonar (TFPs) podem ajudar a identificar o nível de deterioração no período pós-TCTH. (7) Embora a tomografia computadorizada (TC) seja o método de escolha para detectar anormalidades pulmonares, os achados tomográficos geralmente são inespecíficos e requerem correlações temporais baseadas no estado imune do paciente. (5,6,8) Foi realizada uma revisão retrospectiva de todos os pacientes menores de 14 anos que receberam TCTH em um centro de referência no período de 2013 a A TC de tórax foi realizada em 75 (46,6%) pacientes no acompanhamento pós-transplante, dos quais 61 (81,3%) apresentavam anormalidades.…”
Section: Ao Editorunclassified
“…(10) Jung et al (2021) mostraram que alterações no VEF1 nos primeiros 3 meses após o diagnóstico de BO impactaram desfechos como óbito e transplante de pulmão, indicando a necessidade de monitoramento e intervenções mais precoces para alterar os indicadores de sobrevida. (7) As alterações tomográficas de tórax encontradas foram destacadas em revisões anteriores, principalmente 2/3…”
Section: Carta Ao Editorunclassified